2023
DOI: 10.3390/ijms241612962
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Reinfections and Long COVID in the Post-Omicron Phase of the Pandemic

Fotini Boufidou,
Snežana Medić,
Vicky Lampropoulou
et al.

Abstract: We are reviewing the current state of knowledge on the virological and immunological correlates of long COVID, focusing on recent evidence for the possible association between the increasing number of SARS-CoV-2 reinfections and the parallel pandemic of long COVID. The severity of reinfections largely depends on the severity of the initial episode; in turn, this is determined both by a combination of genetic factors, particularly related to the innate immune response, and by the pathogenicity of the specific v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 116 publications
0
12
0
Order By: Relevance
“…A recent prospective study demonstrates similar findings, in which patients with high respiratory symptomatic burden 3-months post-COVID were associated with high disease severity 40 . Previous studies have reported individuals with mild symptoms from SARS-CoV-2 infection (i.e., not requiring hospitalization) or asymptomatic infection may also be susceptible to general and neurological PASC 41 43 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent prospective study demonstrates similar findings, in which patients with high respiratory symptomatic burden 3-months post-COVID were associated with high disease severity 40 . Previous studies have reported individuals with mild symptoms from SARS-CoV-2 infection (i.e., not requiring hospitalization) or asymptomatic infection may also be susceptible to general and neurological PASC 41 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The above is important because asymptomatic cases have the potential to perpetuate infections among vulnerable individuals or those who might eventually develop symptomatic disease. Moreover, this is crucial considering studies suggesting that reinfections could elevate the long-term risk of COVID-19, albeit to a lesser extent in mild or asymptomatic infections [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to host factors such as immunity status, comorbidities, vaccination status etc., Long COVID is also influenced by the virus, including strain/variant ( 180 ). Therefore, it is important to distinguish between long COVID infections with the wild type virus and subsequent variants.…”
Section: Risk Factors For Long Covid-19mentioning
confidence: 99%